Cohesion and Structure in the Pastoral Epistles. By Ray Van Neste - Towner, Philip H. (The journal of theological studies, 2007)
In the past twenty five years or so, the ‘Pastoral Epistles’ have been subjected to numerous tests of background, exegesis, and theology in the effort to prove, improve or disprove the adequacy of their interpretation which has come to be the scholarly consensus. This consensus is of course shaped by decisions about pseudonymity, post-apostolic setting, ethics, developments or diminishment in Pauline theology, etc., but the structure of the letters, as such, has more often been relegated to commentary introductions, so Dr Van Neste's thorough discourse-analytical examination of the coherence and structure of each letter is an important contribution to filling a noticeable gap in the research.